Pelatihan Penyusunan LAKIP Berperspektif Gender di Pemerintah Kabupaten Lampung Tengah - Handy Mulyaningsih; Simon Sumanjoyo Hutagalung; Rahayu Sulistiowati; Eko Budi Sulistio (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: this activity aims to: (1). Optimizing the capacity of the district government apparatus group so that they have the knowledge to identify and compile development planning documents in each regional apparatus organization (OPD), (2). Increase the capacity of district government apparatus groups in identifying and compiling development planning documents in each regional apparatus organization (OPD). Methodology: Community service activities are carried out in the form of training with a theoretical pragmatic approach and a practical pragmatic approach. In the implementation phase, the main activities carried out are the delivery of materials, training, and practice. Results: From the results of the activity it is known that most of them gave an enthusiastic response and provided positive feedback by demonstrating their ability to compose development planning narratives with a gender perspective in the Central Lampung Regency environment. Conclusion: This activity is able to achieve the desired goals before.